A genealogy of fish women and other imagined identities: “The mechanics of fluids” in Larissa Lai's Salt Fish Girl - Ma, Qianyi (Orbis litterarum, 2025)
Fluidity invigorates a utopian home in Chinese Canadian author Larissa Lai's Salt Fish Girl (2002). In the novel, the fishlike lesbian couple cyclically returns to their aquatic habitat between mortal reincarnations: from last‐century colonial South China to near‐future bio‐capitalistic Canada, where they recurrently experience displacement. While previous studies interpret the titular Salt Fish Girl as a rebellious figure due to her saltfish stink in all her human incarnations, my study does not consider malodor for its disruptive qualities. I propose that the saltfish smell signifies less a symbolic marker of rebellion than a sign of displacement. Naturally, fish do not reek in their homely waters; fish stink once caught and die ashore. Fish heroines, therefore, emerge as diasporic figures, representing those who experience a permanent sense of displacement on earth because of their ethnicity, gender, and more factors. My study shows that in Lai's novel, fluidity constitutes a symbolic habitable space for imagining more than the reified identities within the real‐world gender binary, ethnic categories, national rhetoric, and even “humanism.” While both Chinese and Canadian landscapes in Lai's depictions prove unlivable for ethnic queer women, my study explores the fluid habitat where the fish heroines can be constantly reborn before they vengefully land on earth.